Youth Involvement in Processing Kitchen Waste into Eco-Enzyme as Air Freshener in Sanur Kauh Village -Denpasar City - I Nengah Muliarta; Desak Ketut Tristiana Sukmadewi; Gede Agus Surya Pratama; I Nyoman Yoga Parawangsa; Ni Luh Putu Putri Setianingsih (Asian Journal of Community Services, 2023)
The community service carried out in Sanur Kauh Village, Denpasar-Bali aims to increase the knowledge and skills of village youth in managing household waste and utilizing it in eco-enzymes. Youth involvement in waste sorting at the household level is still low, the evidence being that only 7% of youth are regularly involved in waste sorting. The youth argued that waste management in the household was already carried out by parents. 2 young people had attended eco-making training but had never put it into practice because they had only attended the training once. Eco-enzyme production from fruit and vegetable waste, apart from being able to reduce the volume of waste, also produces products of economic value. One of the eco-enzymes can be used as an air freshener.